Dancing for a Cause: Examining the Role of K-Pop in Mobilizing Youth for Charitable Giving during Ramadan - Agoes, Adrian; Khansa, Diva (Journal of Event, Travel and Tour Management, 2024)
This research investigates the success of the "K-POP Dance Cover Showcase & Charity Event (SxS Ngabuburit Vol. 2)" as a case study within event tourism, focusing on its utilization of Ramadan as a catalyst for charitable giving. Grounded in a participatory approach, the researcher, actively involved in event planning and execution, augmented findings with interviews of the organizing leader. The event, held within a local community, attracted 20 dance groups and 300 spectators, raising Rp. 2.6 million for charity, solely from local participants. K-Pop's global influence transcends entertainment, extending to philanthropic endeavors. The integration of K-Pop with charitable initiatives, especially within a local context, remains underexplored. A participatory approach intertwined with semi-structured interviews was adopted. The researcher's involvement from planning to execution provided first-hand insights, while interviews with the organizing leader unveiled motivations and operational intricacies. Ramadan served as a pivotal driver, harnessing spiritual values to mobilize youth towards charitable acts. The event exemplified communal solidarity and social consciousness, transcending cultural boundaries. Operational insights highlighted strategic alignment with Ramadan's temporal significance, guiding decision-making processes. This study elucidates the success of the "SxS Ngabuburit Vol. 2" event, showcasing how the integration of K-Pop with Ramadan charity initiatives fosters community engagement and philanthropy. Recommendations include leveraging cultural and temporal contexts to maximize impact in future event planning.